Noninvasive Pneumococcal Pneumonia in Adults in Portugal (2012–2015): Resilience of Vaccine Serotypes and Emergence of Non-vaccine Serotypes. (4th October 2017) - Horácio, Andreia N; Silva-Costa, Catarina; Lopes, Joana P; Ramirez, Mario; Melo-Cristino, Jose; ,
Abstract: Background: The 13-valent pneumococcal conjugate vaccine (PCV13) is available in Portugal through the private sector for children since 2010. In 2015 it was included in the national immunization program for children. With the aim of evaluating a possible herd effect, we monitored the serotypes and antimicrobial resistance of isolates (2012–2015) causing noninvasive pneumococcal pneumonia (NIPP) in adults (≥ 18 yrs). Methods: 1435 adult NIPP isolates were recovered, serotyped by the Quellung reaction and tested for susceptibility to antimicrobials by disk diffusion or Etest. Results: There were 50 different serotypes among the 1435 isolates. The most common were serotypes 3 (14%), 11A (8%), 19F (6%), 23A (5%), 6C (5%), 19A (4%), 23B (4%) and 9N (4%). Non-typable isolates accounted for 4% of the collection. The overall proportion of PCV13 serotypes declined from 44% in 2010 to 30% in 2015 (P < 0.001) although it remained relatively stable in 2012–2015. Several serotypes exhibited strong fluctuations in 2007–2015, suggesting that adult NIPP was under the influence of both vaccine-related and non-vaccine-related pressures. PCV7 serotypes (12% in 2012–2015) and the serotypes exclusively found in the 23-valent polysaccharide vaccine (26% in 2012–2015) did not change significantly in 2007–2015, while non-vaccine types increased in proportion (from 27% in 2010 to 42% in 2015, P < 0.001). Penicillin non-susceptibility and erythromycin resistance was found in 18% and 22% of the isolates recovered in 2012–2015, with no significant changes seen since 2007. Conclusion: While a significant fraction of NIPP is still caused by vaccine serotypes, the availability of PCV13 in the national immunization program for children from 2015 onwards may further reduce their importance in NIPP, questioning the need for adult vaccination. Disclosures: M. Ramirez, Pfizer: Speaker's Bureau, Speaker honorarium; GSK: Consultant, Consulting fee; J. Melo-Cristino, Pfizer: Grant Investigator, Independent Contractor and Speaker's Bureau, Grant recipient, Research grant and Speaker honorarium; GSK: Grant Investigator and Speaker's Bureau, Grant recipient and Speaker honorarium; Bial: Speaker's Bureau, Speaker honorarium; Novartis: Speaker's Bureau, Speaker honorarium